The effectiveness of online platform method in delivering pre-operative exercise among anterior cruciate ligament tear individuals - Nurul Atiqah Ayni Ayob (Tanjong Malim, 2023)
The effectiveness of online platform method in delivering pre-operative exercise among anterior cruciate ligament tear individuals by Nurul Atiqah Ayni Ayob